2014
DOI: 10.1515/zkri-2014-1802
|View full text |Cite
|
Sign up to set email alerts
|

A DFT-D study of the interaction of methane, carbon monoxide, and nitrogen with cation-exchanged SAPO-34

Abstract: Density-functional theory calculations including a semi-empirical dispersion correction (DFT-D) are employed to study the interaction of small guest molecules (CH 4 , CO, N 2 ) with the cation sites in the silicoaluminophosphate SAPO-34. Eight different cations from three different groups (alkali cations, alkaline earth cations, transition metals) are included in the study. For each case, the total interaction energy as well as the non-dispersive contribution to the interaction are analysed. Electron density d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The most accurate description is achieved at the RPA level with Hartree–Fock (HF) exchange energies (RPA-HF) . Later, they found similar trends for the small alkanes in protonated CHA. The overestimation of adsorption energies using PBE-D2 or -D3 and a variety of vdW-DF approaches have also been observed for CH 4 in silicalite, HZSM-5, MOR, ZSM-12, and SAPO-34 zeolites. …”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…The most accurate description is achieved at the RPA level with Hartree–Fock (HF) exchange energies (RPA-HF) . Later, they found similar trends for the small alkanes in protonated CHA. The overestimation of adsorption energies using PBE-D2 or -D3 and a variety of vdW-DF approaches have also been observed for CH 4 in silicalite, HZSM-5, MOR, ZSM-12, and SAPO-34 zeolites. …”
Section: Methodsmentioning
confidence: 86%
“…We chose adsorption of CH 4 in Si-CHA ( R 3̅ m space group) as the benchmark system because the computational cost for this material using its primitive unit cell is lower than that of many other zeolites. For this reason, CHA zeolites have been often used for the benchmarking of QM methods. Among these studies, Göltl et al investigated the adsorption of CH 4 and other small alkanes in purely siliceous and Na-exchanged CHA at different levels of theory, including the standard density functional Perdew–Burke–Ernzerhof (PBE), dispersion-corrected PBE-D2, van der Waals (vdW)-DF, and the random phase approximation (RPA) in combination with the adiabatic-connection fluctuation-dissipation theorem using wave-functions . They found that the PBE method underestimates the strength of the interactions between these small alkanes and zeolites, whereas PBE-D2 and vdW-DF strongly overestimate the adsorption energies.…”
Section: Methodsmentioning
confidence: 99%
“…In Na-CHA, a significant portion of the cages is occupied by cations, which reduces the effective cage size and also results in a more negative adsorption enthalpy. 36,41,69,70 In contrast, in Na-SSZ-13 and Si-CHA, the cages are predominantly made from silica tetrahedra, mostly without alumina tetrahedra and their associated cations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%